Розробка алгоритму подання геометричної інформації рухомих рознімних з'єднань для побудови креслеників згідно з ЄСКД при автоматизованому проектуванні - Іванов, Євген Мартинович (НТУ "ХПІ", 2018)
Використання розроблених 3D-моделей складальних одиниць елементів шліцьового з’єднання в параметричних оболонках при побудові 3D-моделі шліцьового з’єднання в пакеті Autodesk Inventor, де ескізна геометрія елементів шліцьового з’єднання представлена як функція основних геометричних параметрів, дозволило розробити алгоритм подання геометричної інформації для удосконалення виконання робочих креслеників шліцьових з’єднань згідно з вимогами ЄСКД. Отримав подальший розвиток метод оптимізації розробки конструкторської документації на стадії проектування – метод параметричної оболонки.

This document discusses the issue of improving the construction of drawings on 3D models of the slotted joints, obtained using the masters of the design package Autodesk Inventor. One of the main difficulties in the process of using the package is the presentation of geometric information on the drawing in accordance with the requirements of the Unified System of Project Documentation (USDD). The article describes an algorithm developed to improve the construction of working drawings of the slotted joints. A parametric approach was used to build a 3D model the of slotted joints using the developed 3D models elements in parametric shells in the Autodesk Inventor package, where the sketches geometry the elements is represented as a function of the basic geometric parameters. This allowed to, develop an algorithm for supplying geometric information to improve the execution of working drawings of the slotted joints in accordance with the requirements of USDD. The parametric approach, when solving the problem, allows expanding the application of parametric 3D-shells, namely the ability to create drawings the slotted joints with arbitrary initial parameters in accordance with the requirements of USDD. The method enhanced of optimizing the development of design documentation at the design stage – the method of parametric shell.
Development of an algorithm for representing geometric information of movable detachable connections for constructing drawings in accordance with USDD for computer-aided design
Keywords: шліці; оболонка валу; оболонка отвору; з'єднання шліцьове; алгоритм; Autodesk Inventor; tooth; shell; shaft; hole; splined connection; algorithm